Effect of Intranasal Calcitonin in a Patient with McCune-Albright Syndrome, Fibrous Dysplasia, and Refractory Bone Pain - Tayane Muniz Fighera; Poli Mara Spritzer (Case Reports in Endocrinology)
McCune-Albright syndrome (MAS) is a rare disease defined by the triad of polyostotic fibrous dysplasia of bone, café-au-lait skin spots, and precocious puberty. No available treatment is effective in changing the course of fibrous dysplasia of bone, but symptomatic patients require therapeutic support to reduce bone pain and prevent fractures and deformities. We report the case of a 27-year-old woman with MAS and severe fibrous dysplasia. She was diagnosed with MAS at 4 years of age and, during follow-up, she had multiple pathological fractures and bone pain refractory to treatment with bisphosphonates, tricyclic antidepressants, and opioids. The pain was incapacitating and the patient required a wheelchair. Intranasal calcitonin was then started, and, 30 days later, the patient already showed significant improvement in pain severity at the affected sites. After 3 months, she was able to walk without assistance. No adverse effects were observed, nor were any significant changes in serum levels of calcium, phosphorus, and alkaline phosphatase. Calcitonin has a well-recognized analgesic effect on bone tissue. Despite the small number of studies involving patients with MAS, calcitonin may be considered a short-term therapeutic option in cases of severe and refractory bone pain.